Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 18. Beitrag: Dermaptera. - Brindle, Alan; Friese, Gerrit (Contributions to Entomology = Beiträge zur Entomologie, 1964)
There is given a survey of the Dermapterous fauna of the Balkan countries and - based upon the material of the expedition of the Deutsches Entomologisches Institut - of the Dermaptera of Albania. The expedition collected 41 specimens of 4 species, including Forficula smyrnensis Serville which was known only from Greece. There are further mentioned 2 specimens found by Ing. J. Grebenscikov 1958 and Prof. Dr. U. Sedlag 1960 respectively in Albania.